The Influence of Leadership Democracy, Work Discipline and Work Environment on Individual Employee Performance in PT. Indosino Agrochemical - Handayani, Mega Putri; Nugroho, Prayekti (LPPM Universitas Bina Bangsa, 2022)
This study aims to determine the effect of democratic leadership, work discipline, and work environment on individual employee performance. This type of research is quantitative. The population in this study were employees of PT. Indosino Agrochemical. Data collection is done by distributing online questionnaires to employees, data directly obtained from respondents. The results of this study indicate that (1) democratic leadership has a significant effect on individual employee performance, (2) work discipline has an effect on individual employee performance, (3) work environment has no significant effect on individual employee performance